Analisis Faktor yang Berhubungan dengan Kepatuhan Calon Pengantin dalam Melaksanakan Imunisasi TT di Puskesmas Driyorejo - Aushaf, Nasywa Fitria; Setyowati, Dewi; Umiastuti, Pirlina; Anis, Wahyul (JUKEJ : Jurnal Kesehatan Jompa, 2026)
Tetanus Toxoid (TT) immunization in the bride-to-be is an important effort to prevent tetanus in mothers and babies. However, TT immunization coverage at WUS in Gresik Regency in 2023 is only 83.2%, still below the target of 90%. This condition is influenced by various factors. This study was conducted with the aim of analyzing factors related to the compliance of the bride-to-be in carrying out TT immunization in the working area of the Driyorejo Gresik Health Center. The method used was observational with a cross sectional design. The number of respondents was 64 brides-to-be who met the inclusion criteria, namely aged 15-49 years and visited the Driyorejo Gresik Health Center in the period of June-August 2025. Data analysis uses chi-square test and fisher exact test if they do not meet the requirements of chi square test. The results of the bivariate analysis of the knowledge level p=0.348, the support of the prospective husband p=0.021, work p=0.322, the role of health workers p=0.014, and the attitude of p=0.081 towards the compliance of the bride-to-be in carrying out the completeness of TT immunization. Based on these results, there is a significant relationship between the support factor of the prospective husband and the role of health workers on the compliance of the bride-to-be in carrying out TT immunization. There was no significant relationship between knowledge, work, and attitude factors towards the bride-to-be's compliance in carrying out TT immunization at the Driyorejo Gresik Health Center.